Loss of PTEN expression is associated with colorectal cancer liver metastasis and poor patient survival - Funahashi Hitoshi; Takahashi Hiroki; Wakasugi Takehiro; Matsuo Yoichi; Ma Jiachi; Ochi Nobuo; Yasuda Akira; Sawai Hirozumi; Sato Mikinori; Takeyama Hiromitsu (BMC Gastroenterology, 2008)
Abstract Background The tumour suppressor phosphatase and tensin homolog (PTEN) is an important negative regulator of cell-survival signaling. To evaluate the correlation between PTEN expression and clinicopathological characteristics of colorectal cancer patients with and without liver metastases, we investigated PTEN expression in primary colorectal cancer and colorectal cancer liver metastases. Methods Sixty-nine pairs of primary colorectal cancer and corresponding liver metastasis specimens were analyzed immunohistochemically, and the correlation between immunohistochemical findings and clinicopathological factors was investigated. Seventy primary colorectal cancer specimens from patients without liver metastases were used as controls. Results PTEN was strongly expressed in 44 (62.9%) colorectal cancer specimens from patients without liver metastases. In contrast, PTEN was weakly expressed in 52 (75.4%) primary colorectal cancer specimens from patients with liver metastases, and was absent in liver metastases. Weak PTEN expression in colorectal cancer tissues was significantly associated with advanced TNM stage (p < 0.01) and lymph node metastasis (p < 0.05). PTEN expression was significantly stronger in primary colorectal cancer specimens from patients without liver metastases. Furthermore, among colorectal cancer patients with liver metastases, the 5-year survival rate was significantly higher in patients with positive PTEN expression compared to those with negative PTEN expression (p = 0.012). Conclusion Our results suggest that loss of PTEN expression is involved with colorectal cancer aggressive capacity and that diagnostic evaluation of PTEN expression may provide valuable prognostic information to aid treatment strategies for colorectal cancer patients.